Factors Influencing the Interactions in Gelatin/Hydroxyapatite Hybrid Materials - Zhang, Zixin; Li, Kexin; Zhou, Weixian; Gu, Jin'ge; Liu, Ying; Han, Charles C.; Xu, Shanshan (Frontiers in Chemistry, 2020)
The most severe problem in bone regeneration is the defect in the interface. We prepared four types of implantation scaffolds of crosslinked gelatin (GE)/hydroxyapatite (HAp) to study the factors influencing interface interactions, they are film-crosslinked GE scaffold, gel-crosslinked GE scaffold, solid-crosslinked GE/HAp scaffold and gel-crosslinked GE/HAp scaffold. HAp could penetrate the entire GE matrix completely in four successive steps: physical preparation of a gel; chemical crosslinking; incubation in modified simulated body fluid (m-SBF) and freeze-drying. The penetrative nucleation and growth of HAp and the influencing factors in the GE matrix were investigated to ameliorate the interface interactions between organic and inorganic layers. During development of penetrative nucleation and growth, a tight connection was built between organic and inorganic layers, B-type carbonated HAp was formed after incubation with m-BSF, and the apatite content could be controlled. In summary, enhanced interface relies on not only the pre-seeded hydroxyapatite (HAp) as crystal nuclei but also the sufficient space for ions with high concentration to diffuse in.